Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1111/j.2042-3306.1981.tb03455.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine congenital cutaneous papillomatosis: A report of 5 cases

Abstract: Résumé Quatre cas de papillomatose equine congenitale ont été identifiés parmi 555 tumeurs cutanées observées dans le département de pathologie du Collège Vétérinaire de L'Université d'Ontario, au cours d'une période de 10 années. Un cinquième cas a été observé au delà de la dite période. Deux tumeurs de ce type furent trouvées chez des Pur Sang, une chez un Standardbred, une chez une Arabe et un autre cas chez un animal dont la race ne fut pas précisée. Les localisations anatomiques furent la cage thoracique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
1
13
0
2
Order By: Relevance
“…[1][2][3] In utero infection by a latent papillomavirus in the dam has been proposed as a possible cause. 1,[4][5][6][7][8] A study that included five cases of equine congenital papilloma found no immunohistochemical evidence of papillomavirus, 6 which supports the suggestion that these lesions are a form of epidermal nevus. 3 The purpose of this study is to describe gross pathological and histopathological findings and results of immunohistochemistry for detection of papillomavirus in five additional cases of equine congenital papilloma, including one case in a foetus.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…[1][2][3] In utero infection by a latent papillomavirus in the dam has been proposed as a possible cause. 1,[4][5][6][7][8] A study that included five cases of equine congenital papilloma found no immunohistochemical evidence of papillomavirus, 6 which supports the suggestion that these lesions are a form of epidermal nevus. 3 The purpose of this study is to describe gross pathological and histopathological findings and results of immunohistochemistry for detection of papillomavirus in five additional cases of equine congenital papilloma, including one case in a foetus.…”
Section: Introductionmentioning
confidence: 71%
“…Congenital squamous papilloma occurs most often in horses. [1][2][3][4][5][6][7][8][9] Congenital fibropapilloma occurs rarely in pigs 13 and cattle. 14 The gross pathological findings in these five cases of equine congenital papilloma are similar to those described previously.…”
Section: Discussionmentioning
confidence: 99%
“…This form may occur in an enzootic form (5 (18,42) or not recognized (56). It is conceivable however, that papillomavirus might occasionally exist in a latent form in utero and becomes manifest when fetal skin attains a critical level of maturation (56 (23,28,29,69).…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…In particular, bovine papilloma virus (BPV) types 1, 2, and 5 induce fibropapilloma of the skin in cattle [4,6]. Congenital papillomas are considered non-infectious lesions that most often occur in horses [5,14,17]. In a previous report on porcine congenital papilloma, the presence of virus was not found on electron microscopy, but there have been no studies using immunohistochemistry or polymerase chain reaction (PCR) to assess for viral involvement [16].…”
mentioning
confidence: 99%